2016
DOI: 10.12659/msm.898422
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Leukocytes Interleukin-1 Beta (IL-1β) Cytokine Hyper-Reactivity in Chronic Periodontitis

Abstract: BackgroundLevels of pro-inflammatory cytokine (IL-1β) released by peripheral blood leukocyte medium (PBLM), isolated from chronic periodontitis patients (P) before therapy and matched to controls, were determined in the presence or absence of non-opsonized Escherichia coli and Staphylococcus aureus.Material/MethodsIn this investigation, 26 patients with untreated, severe, generalized, chronic periodontitis and 26 healthy subjects (H) were enrolled. Periodontal status was assessed by measuring bleeding on probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…M1 macrophages release the pro-inflammatory cytokines amplifying inflammation in the PAPT milieu ( He et al, 2020 ; Wang L. et al, 2020 ). The higher levels of pro-inflammatory cytokines in PAPT aggravate periodontitis and alveolar bone loss ( Fredriksson et al, 2002 ; Azuma et al, 2014 ; Sakalauskiene et al, 2016 ; Wang D. et al, 2020 ). Chemotactic molecules CCL2, CCL3, and CCL4 play roles in the infiltration of macrophages and other immune cells in PAPT ( Repeke et al, 2010 ; Parisi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages release the pro-inflammatory cytokines amplifying inflammation in the PAPT milieu ( He et al, 2020 ; Wang L. et al, 2020 ). The higher levels of pro-inflammatory cytokines in PAPT aggravate periodontitis and alveolar bone loss ( Fredriksson et al, 2002 ; Azuma et al, 2014 ; Sakalauskiene et al, 2016 ; Wang D. et al, 2020 ). Chemotactic molecules CCL2, CCL3, and CCL4 play roles in the infiltration of macrophages and other immune cells in PAPT ( Repeke et al, 2010 ; Parisi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the severity of inflammation of peri-implant tissues, appropriate indicator can be IL-1β as it is a pro-inflammatory cytokine which regulates the degradation of the connective tissue and modulates the reparative activity indicating the endothelial cells to cause proliferation of fibroblasts and chemotaxis of neutrophils in inflamed gingiva. The levels of IL-1β can help measure the severity of inflammatory periodontal disease [21]. The concentrations of IL-1β in peri-implant crevicular fluid (PICF) are seen to be at a higher level even in the very first stages of peri-implantitis; the inclination for it later to increase is seen related to the progression of the disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hank’s balanced salt solution were from Sigma Chemical Co. (St. Louis, MO, USA) and plastic vials were from Carl Rot GmbH & Co. KG (Karlsruhe, Germany) [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The problem is that according to many modern studies, there is a positive correlation between inflammatory periodontal disease and many systemic diseases. [3][4][5][6] In the Suzuki et al [7] research it is shown that the infectious periodontitis is associated with hypertrophy of the myocardium due to the activation of metalloproteinase-2. Another group of researchers Li et al [8] is proved that patients with acute myocardial infarct have significantly worse periodontal status.…”
Section: Original Articlementioning
confidence: 99%